The market for underutilised crops - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Devil?s Claw is a desert growing plant that is now in demand for the medicinal properties of its roots. Traditionally used by people in Namibia, demand in Europe is leading to over-harvesting, not least because the plant is very slow growing, making the establishment of commercial production very difficult. Meanwhile, the market for leafy vegetables in Cote D?Ivoire ? and other parts of Africa ? is limited, because they have not yet become popular with young people.